Field-Based Performance Analysis of Turbofan Engines Operating in Tropical Indonesian Commercial Aviation. - Aries Putra Pramadya; Andi Theda Mufarrihah Anwar; Hadi Prayitno (Fakultas Teknik Universitas PGRI Banyuwangi, 2026)
This study presents a field-based performance analysis of turbofan gas turbine engines operating in Indonesia’s commercial aviation sector under tropical environmental conditions. The research focuses on how ambient temperature, humidity, operational frequency, and short-haul flight patterns influence actual engine performance relative to ideal thermodynamic expectations. A mixed-method design was applied by combining literature-based Brayton-cycle modeling with empirical operational data from CFM56 and V2500 engine families. Data sources included engine logbooks, maintenance records, operational observations, and ambient condition monitoring at selected Indonesian airports. The analysis shows that actual specific fuel consumption (SFC) was consistently 5-10% higher than theoretical estimates under high-temperature operating conditions, particularly above 30 °C. Field observations also indicated reduced thrust margins, increased exhaust gas temperature (EGT), and decreasing propulsive efficiency during high-load flight phases, especially takeoff and climb. These deviations confirm that tropical operating conditions and repetitive short-sector utilization accelerate performance deterioration beyond ideal-cycle assumptions. The main scientific contribution of this study is the demonstration that Brayton-cycle-based turbofan performance prediction for Indonesian commercial aviation requires correction for local environmental and operational factors. The findings support the use of climate-adaptive performance assessment and condition-based maintenance strategies to improve engine efficiency, reliability, and operational safety.